2018
DOI: 10.1096/fj.201700888r
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of glycolysis by inhibition of oxygen‐sensing prolyl hydroxylases protects alveolar epithelial cells from acute lung injury

Abstract: Cellular bioenergetic failure caused by mitochondrial dysfunction is a key process of alveolar epithelial injury during acute respiratory distress syndrome (ARDS). Prolyl hydroxylases (PHDs) act as cellular oxygen sensors, and their inhibition activates hypoxia-inducible factor (HIF), resulting in enhanced cellular glycolytic activity, which could compensate for impaired mitochondrial function and protect alveolar epithelial cells from ARDS. Here, we evaluated the effects of pharmacological PHD inhibition with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Recent evidence also has confirmed that patients with sepsis tend to have high levels of NEAT1, increased disease severity, and poor prognosis [13]. LPS-induced endotoxemia is a major inducer of ALI; thus, exposing AECs to LPS has been comprehensively applied as an in vitro model to investigate this condition [3,20]. We corroborated high expression of NEAT1 in LPS-exposed AECs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent evidence also has confirmed that patients with sepsis tend to have high levels of NEAT1, increased disease severity, and poor prognosis [13]. LPS-induced endotoxemia is a major inducer of ALI; thus, exposing AECs to LPS has been comprehensively applied as an in vitro model to investigate this condition [3,20]. We corroborated high expression of NEAT1 in LPS-exposed AECs.…”
Section: Discussionsupporting
confidence: 74%
“…Pulmonary alveolar epithelial cells (AECs) facilitate normal breathing by synthesizing and secreting surfactants. Accumulating evidence has corroborated that the pathophysiological process of ALI is characterized by AEC insult [3,4]. For example, AEC lesions disrupt cellular integrity and the ability to clear fluid from the alveolar space, clinically translating into lung edema.…”
Section: Introductionmentioning
confidence: 99%
“…Bundles of studies observed mitochondrial dysfunction of airway epithelial cells (AECs) in ALI/ARDS. 5,9,10 Moreover, rescuing AECs from mitochondrial dysfunction through mitochondria transferring relieved LPS-induced ALI. 11 A more recent report also affirmed that compensation for mitochondrial impairment by enhancing cellular glycolytic activity could protect airway epithelium from acute injury.…”
Section: Introductionmentioning
confidence: 99%
“…11 A more recent report also affirmed that compensation for mitochondrial impairment by enhancing cellular glycolytic activity could protect airway epithelium from acute injury. 10 Therefore, preventing AECs from mitochondrial impairment might provide a promising therapeutic target for ALI/ARDS. In this regard, numerous "drugs" have been documented over the years ranging from mitochondria-targeted cation to triphenylphosphonium (TPP)-conjugated antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…It is well reported that some metabolites are capable of inducing inflammation and regulating the activation of immune cells [7,8]. Kentaro Tojo et al have revealed that the enhancement of glycolysis attenuated the lung tissue injury by protecting alveolar epithelial cells from decline in energy [9]. Their results also indicated that metabolites played an important role in ARDS.…”
Section: Introductionmentioning
confidence: 98%